Scurvy is Back. (November 2018) - Callus, Claire Ann; Vella, Samantha; Ferry, Peter
Background and objective: Scurvy, caused by vitamin C deficiency, first described by Hippocrates, is known to many as 'The Pirates' Disease'. Although a disease rarely acknowledged in modern medicine, we present 2 cases of elderly gentlemen found to have scurvy, who improved significantly on treatment. Methods: This study presents a case report of 2 patients undergoing rehabilitation at Karin Grech Hospital in Malta, noted to have signs and symptoms of vitamin C deficiency. Vitamin C levels were found to be low and thus supplementation was administered. Results: After a few weeks, a significant improvement was noted in level of frailty, mood, bleeding tendency, and gum health. Conclusions: The modern doctor must keep this ancient disease in mind, as it presents insidiously with debilitating repercussions, particularly in older people who are at a higher risk. It is easily treatable once detected.